2013
DOI: 10.1042/bj20121349
|View full text |Cite
|
Sign up to set email alerts
|

Time-resolved metabolomics analysis of β-cells implicates the pentose phosphate pathway in the control of insulin release

Abstract: Insulin secretion is coupled with changes in β-cell metabolism. To define this process, 195 putative metabolites, mitochondrial respiration, NADP+, NADPH and insulin secretion were measured within 15 min of stimulation of clonal INS-1 832/13 β-cells with glucose. Rapid responses in the major metabolic pathways of glucose occurred, involving several previously suggested metabolic coupling factors. The complexity of metabolite changes observed disagreed with the concept of one single metabolite controlling insul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
109
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 91 publications
(117 citation statements)
references
References 65 publications
7
109
0
1
Order By: Relevance
“…Notably, we found that stimulation of αTC1-6 and INS-1 832/13 cells with glucose provoked increased levels of glutamate and glycerol 3-phosphate and decreased levels of aspartate, confirming previous findings in the INS-1 832/13 cell line [36]. These intermediates are all part of the mitochondrial shuttles.…”
Section: Figure 8 Gsis From Mouse Islets Is Unaffected By Phs Whereasupporting
confidence: 91%
See 1 more Smart Citation
“…Notably, we found that stimulation of αTC1-6 and INS-1 832/13 cells with glucose provoked increased levels of glutamate and glycerol 3-phosphate and decreased levels of aspartate, confirming previous findings in the INS-1 832/13 cell line [36]. These intermediates are all part of the mitochondrial shuttles.…”
Section: Figure 8 Gsis From Mouse Islets Is Unaffected By Phs Whereasupporting
confidence: 91%
“…Metabolite profiling was performed in αTC1-6 and INS-1 832/13 cells as previously described in detail [35,36]. In brief, α-TC1-6 and INS-1 832/13 cells were seeded in 12-and 24-well plates respectively and treated as described for hormone secretion.…”
Section: Metabolite Profilingmentioning
confidence: 99%
“…A similar time course can be seen in the respiratory response of clonal insulinoma cells and human islets to acutely elevated glucose, with an initial doubling of respiration followed by a further increase over the subsequent 50 min (112,184,491). Much of the enhanced proton current is directed through the ATP synthase, rather than the endogenous proton leak, judged by the extent of oligomycin inhibition (FIGURE 3D) (112,147,184,427).…”
Section: If the Effect Of Elevated [Ca 2ϩmentioning
confidence: 69%
“…A relatively low activity does not, of course, invalidate a pathway as long as it is sufficient to meet the ␤-cell's ill-defined NADPH requirements. Spegel et al (491) provided evidence for its significance in INS-1 832/13 cells: following the addition of high glucose, the NADPH/NADP ratio increased in the cells synchronously with the formation of ribose-5-phosphate. However, one difficulty with an obligatory role for the pentose phosphate pathway in facilitating insulin secretion is that alternative substrates, such as ␣-ketoisocaproate or pyruvate (in the case of INS-1-derived cells), are highly effective secretagogues while not providing substrate for the pathway.…”
Section: A Nadph/nadp ؉ Poolsmentioning
confidence: 99%
See 1 more Smart Citation